Quantitative Evaluation of Vacuum-Induced Morphological Changes in Knee-Disarticulation: A Case Study for Personalized Prosthetic Socket Design - Darwich, Mhd Ayham; Nazha, Hasan Mhd; Ibrahim, Kaysse; Kamleh, Lourance; Shash, Maysaa; Ismaiel, Ebrahim (Symmetry (Basel), 2025)
Achieving a best-fit prosthetic socket is essential to comfort, functional performance, and long-term residual limb health in lower-limb amputees. To our knowledge, no previous study has quantitatively compared in vivo residual limb geometry under vacuum versus non-vacuum conditions using high-resolution computed tomography (CT). In this patient-specific case study of a bilateral knee-disarticulation (KD) amputee, both residual limbs were scanned under standardized conditions: one enclosed in a vacuum-compressed sleeve and the contralateral limb untreated as a natural control, thereby minimizing inter-subject variability. CT-based 3D reconstructions enabled volumetric and cross-sectional quantification, including symmetry/asymmetry analysis of paired limbs, while finite element analysis (FEA) assessed the biomechanical consequences for socket performance. Vacuum application resulted in a 4.1% reduction in total limb volume and a 5.3% reduction in mid-thigh cross-sectional area, with regionally asymmetric displacement of soft tissues. FEA demonstrated that vacuum-induced geometry reduced peak Von Mises stresses (27.43 MPa to 15.83 MPa), minimized maximum displacement (1.72 mm to 0.88 mm), and improved minimum factor of safety (~2.0 to ~3.0), while homogenizing contact pressure distribution (peak fell from 2.42 to 1.28 N/mm2). These findings provide preliminary CT-based evidence that vacuum application induces measurable morphological adaptations with implications for socket conformity, comfort, and load transfer. While limited to a single patient, this study highlights the potential of vacuum-induced modeling to inform personalized prosthetic socket design.